Person-centered home-based rehabilitation for persons with Parkinson's disease: A scoping review. (November 2019) - Vaartio-Rajalin, Heli; Rauhala, Auvo; Fagerström, Lisbeth
Abstract: Background: Due to vague, initial symptoms, persons with Parkinson's disease (PD) usually receive a definitive diagnosis after a prolonged period of time. At the time of diagnosis, they have already experienced limitations in activities of daily living and quality of life and are thus in need of immediate rehabilitation. Objective: To describe the existing knowledge on the rehabilitation of persons with PD suitable to a home environment and to describe the person-centeredness, interprofessionality and clinical effectiveness of existing rehabilitation activities. Sources of evidence: 67 full-text papers from the EBSCO, CINAHL, Medline, Google and Google Scholar databases, published in English, Swedish or Finnish between January 2010 and October 2018, were charted (type of rehabilitation, sample, instrumentation, reported effects) and summarized. Results: Rehabilitation through physical activities still appears to be the most common form of rehabilitation, varying from walking to individually tailored exercise programs. The majority of physical rehabilitation activities were conducted outside the home even though they were suitable for a home setting. Physical activities not only improved several physical outcomes but also quality of life, well-being and activities of daily living functions, especially when digital devices were used. Cognitive and psychosocial rehabilitation were much less researched but seen to be an emerging area of research. The focus of rehabilitation seems to lie on persons with PD, not their near-ones. The majority of interventions were planned without discussing in advance with the persons with PD about their preferences, needs or values. Very few interventions were individually tailored or conducted in a home setting, and many studies included patient-recorded outcome measures, but only as secondary to clinical measures. Only a few studies focused on an interprofessional approach to PD rehabilitation, despite the approach being found effective in regard to quality of life for persons with PD. Conclusions: There appears to be a focus on physical outcomes and symptom management in the rehabilitation of persons with PD, even though cognitive and psychosocial well-being are often explored as secondary outcomes. Very few rehabilitation interventions were planned with persons or conducted in a home setting, and no interventions were seen that included near-ones. The majority of interventions were planned without the involvement of persons with PD. Still, many of the studies included patient-recorded outcome measures. Digital devices that assist in physical rehabilitation and an interprofessional approach to rehabilitation yield positive clinical outcomes, which in turn promotes a person-centered and holistic approach to rehabilitation.